Salicylic Acid Targets Protein Phosphatase 2A to Attenuate Growth in Plants - Tan, Shutang; Abas, Melinda; Verstraeten, Inge; Glanc, Matouš; Molnár, Gergely; Hajný, Jakub; Lasák, Pavel; Petřík, Ivan; Russinova, Eugenia; Petrášek, Jan; Novák, Ondřej; Pospíšil, Jiří; et al. (Current biology, 2020)
Plants, like other multicellular organisms, survive through a delicate balance between growth and defense against pathogens. Salicylic acid (SA) is a major defense signal in plants, and the perception mechanism as well as downstream signaling activating the immune response are known. Here, we identify a parallel SA signaling that mediates growth attenuation. SA directly binds to A subunits of protein phosphatase 2A (PP2A), inhibiting activity of this complex. Among PP2A targets, the PIN2 auxin transporter is hyperphosphorylated in response to SA, leading to changed activity of this important growth regulator. Accordingly, auxin transport and auxin-mediated root development, including growth, gravitropic response, and lateral root organogenesis, are inhibited. This study reveals how SA, besides activating immunity, concomitantly attenuates growth through crosstalk with the auxin distribution network. Further analysis of this dual role of SA and characterization of additional SA-regulated PP2A targets will provide further insights into mechanisms maintaining a balance between growth and defense.
Keywords: proteiny huseníčku; Plant Immunity; auxin transport; Salicylic Acid; gravitropism; PP2A; PIN; imunita rostlin; Arabidopsis; protein phosphatase 2A; salicylic acid; Plant Roots; signální transdukce; Arabidopsis Proteins; kyseliny indoloctové; Signal Transduction; kořeny rostlin; auxin; phosphorylation; kyselina salicylová; Indoleacetic Acids; NPR1; Protein Phosphatase 2; proteinfosfatasa 2; immunity